2019
DOI: 10.2319/081018-589.1
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric evaluation of rapid and slow maxillary expansion in patients with BCLP: Secondary data analysis from a randomized clinical trial

Abstract: Objective: To compare the dentoskeletal effects of rapid (RME) and slow (SME) maxillary expansion in patients with bilateral complete cleft lip and palate (BCLP). Materials and Methods: This was a secondary analysis of a previous randomized controlled trial (RCT). Forty-six patients (34 male, 12 female) with BCLP and posterior crossbite (mean age of 9.2 years) were randomly assigned to two study groups. Group RME comprised su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(66 reference statements)
1
3
0
1
Order By: Relevance
“…In the case reported here, the Haas-type expander was selected due to its maximum anchorage that provided stable expansion. 15,16 In addition, apart from the type of expander, the biochemical reaction to expansion includes the cardinal signs and symptoms of inflammation, such as swelling and pain, 17 as verified in the present study. However, the presence of the acrylic part may lead to ischemia with the formation of necrotic lesions followed by pain, the ulceration of palatal mucosa and excessive bleeding.…”
Section: Discussionsupporting
confidence: 73%
“…In the case reported here, the Haas-type expander was selected due to its maximum anchorage that provided stable expansion. 15,16 In addition, apart from the type of expander, the biochemical reaction to expansion includes the cardinal signs and symptoms of inflammation, such as swelling and pain, 17 as verified in the present study. However, the presence of the acrylic part may lead to ischemia with the formation of necrotic lesions followed by pain, the ulceration of palatal mucosa and excessive bleeding.…”
Section: Discussionsupporting
confidence: 73%
“…When patients began their orthodontic treatment before the age of six, they demonstrated a better response in anterior maxillary expansion [24], which resulted in a significant improvement in the dental arch relationship. The clinical findings imply that maxillary expansion using the Quad Helix appliance is an acceptable alternative to conventional rapid maxillary expansion appliances among cleft patients [25][26][27][28][29]. This conclusion is based on the fact that the appliance is able to expand the maxilla more effectively.…”
Section: Discussionmentioning
confidence: 92%
“…This was reported after the active expansion phase had been completed. RME and SME might have similar effects on vertical and sagittal alterations in children with bilateral cleft lip and palate (BCLP), according to the findings of a secondary analysis carried out by the same research group [29].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in angle ANB and an increase in Ptm-A were found after treatment in this study. Previous studies had shown that maxillary expansion might cause the extrusion of the palatal cusps of the posterior teeth, resulting in the clockwise rotation of the mandible and the increase of the mandibular plane angle, SNB angle, and the ANB angle [ 37 , 38 ]. However, the results of this study showed that the ANB angle statistically decreased by an average of 0.5° after treatment.…”
Section: Discussionmentioning
confidence: 99%